Compact Symmetric Objects. III. Evolution of the High-luminosity Branch and a Possible Connection with Tidal Disruption Events - Readhead, A. (Institute of Physics, 2025)
We use a sample of 54 compact symmetric objects (CSOs) to confirm that there are two unrelated CSO classes: an edge-dimmed, low-luminosity class (CSO 1), and an edge-brightened, high-luminosity class (CSO 2). Using blind tests, we show that CSO 2s consist of three subclasses: CSO 2.0, having prominent hot spots at the leading edges of narrow jets and/or narrow lobes; CSO 2.2, without prominent hot spots and with broad jets and/or lobes; and CSO 2.1, which exhibit mixed properties. Most CSO 2s do not evolve into larger jetted active galactic nuclei (AGN), but spend their whole life cycle as CSOs of size ≲500 pc and age ≲5000 yr. The minimum energies needed to produce the radio luminosity and structure in CSO 2s range from ∼10−4M⊙c2 to ∼7 M⊙c2. We show that the transient nature of most CSO 2s, and their birth rate, can be explained through ignition in the tidal disruption events of stars. We also consider possibilities of tapping the spin energy of the supermassive black hole, and tapping the energy of the accretion disk. Our results demonstrate that CSOs constitute a large family of AGN in which we have thus far studied only the brightest. More comprehensive CSO studies, with higher sensitivity, resolution, and dynamic range, will revolutionize our understanding of AGN and the central engines that power them.